Green insurance subsidy for promoting clean production innovation. (1st April 2017) - Wang, Chan; Nie, Pu-yan; Peng, Da-heng; Li, Zheng-hui
Abstract: Green insurance is introduced to advance green development in recent years, and this article addresses the effects of insurance subsidy. With game theory model, some useful results are achieved. First, uncertainty deters firms' innovation, while both mature technology and high production efficiency stimulate firms' innovation. Second, interestingly, green insurance cannot improve innovation and expect profits of firms. But green insurance reduces risk. Finally, both green insurance subsidy and governmental subsidy promotes firms' innovation but green insurance subsidy owns lower risk than direct subsidy to innovate. Highlights: This article addresses the effects of insurance subsidy with game theory model. Uncertainty deters firms' innovation. Green insurance cannot improve the expected profits but reduce risk. Governmental subsidy can promote firms' innovation.